Perlindungan Hukum Terhadap Kreditur Fidusia - Naway, Dian Rizqi Oktaria; Badu, Lisnawaty W.; Mantali, Avelia Rahma Y. (CV. ITTC INDONESIA, 2023)
Fiduciary is a term that has long been known in Indonesian. The law that specifically regulates this matter, namely UUJF also uses the term